Multiple measures of HIV burden in blood and tissue are correlated with each other but not with clinical parameters in aviremic subjects - Anton, Peter A; Mitsuyasu, Ronald T; Deeks, Steven G; Scadden, David T; Wagner, Bridget; Huang, Christine; Macken, Catherine; Richman, Douglas D; Christopherson, Cindy; Borellini, Flavia; Lazar, Richard; Hege, Kristen M (AIDS (London), 2003)
To determine the levels of residual HIV DNA and RNA in blood and gut reservoirs in aviremic patients, assess correlations among compartmental measurements of HIV burden, and evaluate association with clinical parameters. Cross-sectional analysis of baseline data only, on 40 patients enrolled in phase II study evaluating efficacy of autologous gene-modified CD4+ and CD8+ T cells. All patients were on stable antiretroviral regimen with undetectable plasma HIV RNA (< 50 copies/ml). Measurements repeatedly performed over 8-12 weeks pre-intervention: blood HIV DNA, analysis of rectal mucosa-associated lymphoid tissue for both HIV RNA and HIV DNA, and quantitative co-culture of HIV from CD8-depleted peripheral blood mononuclear cells (PBMC). Quantifiable levels of HIV detected in compartments despite undetectable levels of plasma HIV RNA: HIV co-culture of PBMC (88%), blood HIV DNA (95%), rectal biopsy HIV DNA (95%), rectal biopsy HIV RNA (65%). A significant correlation existed among various measures of HIV burden (HIV co-culture, blood HIV DNA, rectal biopsy HIV RNA and DNA) but not between assays and clinical parameters [duration of highly active antiretroviral therapy (HAART), type of HAART]. All assays had comparable or less variability than in plasma viral load assays; HIV co-culture had the highest coefficient of variability whereas the blood HIV DNA assay had the lowest and was considered the most reliable assay. The data support safety, feasibility and high compliance of quantifying reservoirs of residual HIV in treated subjects with undetectable plasma HIV RNA. Lack of correlation between levels of HIV in residual reservoirs and duration of HAART suggests treatment-mediated viral suppression alone does not lead to reproducible decay in HIV reservoirs.